2020
DOI: 10.1101/2020.07.20.212225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MHC class IIa haplotypes derived by high throughput SNP screening in an isolated sheep population

Abstract: Investigating the current evolutionary processes acting on a highly polymorphic gene region, such as the major histocompatibility complex (MHC), requires extensive population data for both genotypes and phenotypes. The MHC consists of several tightly linked loci with both allelic and gene content variation, making it challenging to genotype. Eight class IIa haplotypes have previously been identified in the Soay sheep (Ovis aries) of St. Kilda using Sanger sequencing and cloning, but no single locus is represen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Few previous studies have reported specific MHC variants being favoured or disfavoured during mating as the high polymorphism of MHC genes requires a large sample size to detect sexual selection on specific MHC variants (Eizaguirre, Yeates et al 2009). In this study, our finding for haplotype C in male parents was consistent with a negative association between MHC haplotype C and male breeding success found in a recent study on MHC-fitness associations (Huang, Dicks et al 2020). The fact that haplotype C males are also less often observed in consort than expected indicates that the effect of haplotype C is expressed at the pre-copulatory rather than post-copulatory stage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Few previous studies have reported specific MHC variants being favoured or disfavoured during mating as the high polymorphism of MHC genes requires a large sample size to detect sexual selection on specific MHC variants (Eizaguirre, Yeates et al 2009). In this study, our finding for haplotype C in male parents was consistent with a negative association between MHC haplotype C and male breeding success found in a recent study on MHC-fitness associations (Huang, Dicks et al 2020). The fact that haplotype C males are also less often observed in consort than expected indicates that the effect of haplotype C is expressed at the pre-copulatory rather than post-copulatory stage.…”
Section: Discussionsupporting
confidence: 92%
“…First, seven expressed loci (DRB1, DQA1, DQA2, DQA2-like, DQB1, DQB2 and DQB2-like) within the MHC class IIa region were characterized in 118 Soay sheep using genotyping-by-sequencing which identified eight haplotypes named A to H (Dicks, Pemberton et al 2019). Second, a panel of 13 SNPs located in the MHC class IIa region haplotypes including 11 SNPs from the Ovine Infinium high density SNP array (Illumina) and two other SNPs located within DQA1 gene were selected to impute eight haplotypes using Kompetitive Allele-specific PCR (KASP) in 5951 Soay sheep (Dicks, Pemberton et al 2020). After genotyping quality control and pedigree checking, 5349 individuals were successfully diplotyped.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A panel of 13 SNPs located in the region of MHC class IIa haplotypes was then selected to impute the eight MHC class IIa haplotypes in 5951 Soay sheep genotyped using Kompetitive Allele-specific PCR (KASP). This panel included 11 SNPs known to be variable in Soays based on data from the Illumina Ovine infinium HD chip and two other SNPs identified within the DQA1 gene (52). After quality control, the diplotypes of 5349 individuals that lived in the study area between 1985 and 2012 were identified.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic data used in this study was obtained from a previous study (Dicks, Pemberton et al 2019, Dicks, Pemberton et al 2020). Seven expressed loci ( DRB1, DQA1, DQA2, DQA2-like, DQB1, DQB2 and DQB2-like ) within the MHC class IIa region were characterised in 118 Soay sheep using sequence-based genotyping.…”
Section: Methodsmentioning
confidence: 99%